2013
DOI: 10.1016/j.molcel.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control of Persister Formation in Escherichia coli

Abstract: Bacterial persisters are phenotypic variants that form from the action of stress response pathways triggering toxin-mediated antibiotic tolerance. Although persisters form during normal growth from native stresses, the pathways responsible for this phenomenon remain elusive. Here we have discovered that carbon source transitions stimulate the formation of fluoroquinolone persisters in Escherichia coli. Further, through a combination of genetic, biochemical, and flow cytometric assays in conjunction with a math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
343
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(363 citation statements)
references
References 62 publications
16
343
4
Order By: Relevance
“…3d). Factors such as quorum sensing, cell density, nutrient starvation, diauxic carbon source transitions, environmental signals (such as heat shock, oxidative stress and DNA damage) and stringent response pathways contribute to microbial persistence in vitro [54][55][56][57][58][59] . TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…3d). Factors such as quorum sensing, cell density, nutrient starvation, diauxic carbon source transitions, environmental signals (such as heat shock, oxidative stress and DNA damage) and stringent response pathways contribute to microbial persistence in vitro [54][55][56][57][58][59] . TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have begun to revise this view with the demonstration that even non-, or slowly, replicating bacteria could be rendered sensitive to antibiotics. Studies of Escherichia coli, Staphylococcus aureus and even Mtb have shown that the activity of many antibiotics: (i) is dependent on the activity of specific metabolic pathways, (ii) differs for replicating and nonreplicating populations and (iii) can be dissociated from growth rate 7,12,27 . In Mtb, it was shown that adaptation to hypoxia was accompanied by a redirection of metabolic flux away from the TCA cycle and towards the generation of triglycerides, whose inhibition resensitized Mtb to antibiotics in absence of growth 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has expanded the scope of physiologic factors associated with antibiotic resistance to include broader bacterial stress responses, such as the SOS DNA stress response, heatshock response and oxidative stress response, as well as changes in metabolic state and activity [7][8][9][10][11][12] . These antibiotic-induced responses then contribute functionally to resistance.…”
mentioning
confidence: 99%
“…The stringent response is a highly conserved mechanism that enables bacteria (1)(2)(3) and plant chloroplasts (4)(5)(6) to respond to nutrient (i.e., amino acid) limitations. However, recent work has indicated that guanosine tetraphosphate (ppGpp) and guanosine pentaphosphate (pppGpp) [collectively named "(p)ppGpp"] also impact other, nonstringent response processes such as virulence (7)(8)(9) as well as persister (10,11) and biofilm formation (12). Realization of the importance of (p)ppGpp has also opened new avenues for the design of antimicrobial agents (13,14).…”
mentioning
confidence: 99%